Analysis of the peculiarities of the communication organization in NATO countries - Bihun, Nataliia; Bogrieiev, Sergii; Nalapko, Oleksii; Sova, Oleg; Trotsko, Oleksandr; Shyshatskyi, Andrii (Національний технічний університет "Харківський політехнічний інститут", 2019)
According to the Military doctrine of Ukraine, one of the central tasks is to reform the Armed Forces of Ukraine in order to achieve interoperability and technical compatibility with the armed forces of NATO member states, as well as adherence to the standards of work, division of functions and core tasks adopted in the EU and NATO member states. Today, there is a need to improve the system of communication between governing bodies in the military management system. However, the slow pace of implementation of NATO standards is significantly hampering this process. One reason for this is the lack of attention to the adaptation of the Ukrainian Armed Forces' operational planning system to similar systems used in NATO countries. The article analyzes the principal principles of the communications organization and discusses the key steps involved in developing an operational plan based on the capabilities of NATO member countries. Since communication planning is one of the major elements of NATO operations planning, the authors of that article analyzed the operational planning of the communications and information system planning, taking into account the need to align Ukraine's Armed Forces management systems with NATO standards. During the research, the authors examined the main steps involved in planning the communications system, identified the factors that influence its planning process. Therefore, a promising direction for further research by the authors should be considered the justification of ways to improve the planning process of the Armed Forces communications system and detailed research of NATO documentation and standards, in terms of organization and planning of communications, in order to explain the requirements for the military management system in Ukraine. This will allow the harmonization (integration) of Ukraine's national development plans with the NATO defense plan.

Відповідно до Воєнної доктрини України,одним з центральних завдань вважається реформування Збройних Сил України для досягнення оперативної та технічної сумісності зі збройними силами країн - членів НАТО, а ще дотримання прийнятих в державах - членах ЄС та НАТО стандартів роботи, розподілу функцій і основних завдань. Сьогодні існує потреба у вдосконаленні системи зв’язку між органами управління в системі управління військами. Проте низькі темпи впровадження стандартів НАТО значно стримують цей процес. Однією з причин цього є недостатнє приділення уваги до адаптації системи оперативного планування Збройних Сил України до аналогічних систем, які використовуються в країнах - членах НАТО. У статті проведено аналіз основних принців організації зв’язку та розглянуто основні етапи з розробки оперативного плану на основі спроможностей країн - членів НАТО. Оскільки, планування зв’язку є однією з основних частин планування операцій в НАТО, автори зазначеної статті провели аналіз оперативного процедур планування системи зв’язку та інформатизації беручи до уваги необхідність наближення систем управління Збройних Сил України до стандартів НАТО. В ході проведеного авторами дослідження розглянуто, основні етапи, які охоплює планування системи зв’язку, визначено чинники, що впливають на процес її планування. Отже, перспективним напрямком подальших наукових досліджень авторів слід вважати обґрунтування шляхів удосконалення процесу планування системи зв’язку Збройних Сил України та детальному вивченню документації та стандартів НАТО, в частині, що стосується організаціїта планування зв’язку, з метою пояснення вимог до системи управління військами в Україні. Це дасть можливість гармонізації (інтегрування) власних національних планів розвитку Збройних Сил України з планом оборони НАТО.
Аналіз особливостей організації зв’язку в країнах НАТО
Keywords: standards; capability; Armed Forces of Ukraine; стандарти; спроможності; Збройні Сили України